Expression of metallothionein isoform 3 (MT-3) determines the choice between apoptotic or necrotic cell death in Cd+2-exposed human proximal tubule cells - Somji, Seema; Garrett, Scott H; Sens, Mary Ann; Gurel, Volkan; Sens, Donald A (Toxicological sciences, 2004)
This laboratory has shown that the third isoform of metallothionein (MT-3) is expressed in the human kidney in situ, including the cells of the proximal tubule. A subsequent analysis of MT-3 expression in cell cultures derived from the human proximal tubule (HPT) demonstrated that mortal HPT cells expressed MT-3, while the HPV-immortalized HK-2 cells had no expression of MT-3. In the present study, the effect of MT-3 expression on Cd(+2)-induced cytotoxicity was determined by stable transfection of the MT-3 coding sequence into the HK-2 cell line. The results demonstrated that HK-2 cells stably transfected with MT-3 were more sensitive to the cytotoxic effects of Cd(+2). Furthermore, this increase in Cd(+2)-induced cytotoxicity was correlated to an alteration in the mechanism of cell death, being changed from an apoptotic mechanism in cells not expressing the MT-3 gene to a necrotic mechanism in cells expressing the MT-3 gene. The present study provides evidence that MT-3 could play a role in controlling the choice between apoptosis and necrosis in multiple epithelial cell types of the human kidney.